Short Version Dental Anxiety Inventory Score May Predict the Response in the Insular Cortex to Stimuli Mimicking Dental Treatment - Yeung, Andy Wai Kan; Lee, Johnson Chun Ming; Tanabe, Hiroki C.; Ng, Sam Kwai Sang; Khong, Pek-Lan; Leung, Wai Keung; Goto, Tazuko K. (Frontiers in Human Neuroscience, 2019)
Background: Dental anxiety is a common reason for avoiding dental visits and is associated with poor dental status. The short version of Dental Anxiety Inventory (SDAxI) is an easy-to-use, multi-faceted questionnaire for assessing the level of trait dental anxiety. However, there was no neurophysiological data indicating if its score associates with the state anxiety when an individual is under real/mock dental environment. We hypothesized that there exists such an association. Materials and Methods: Twenty systemic healthy adults with dental attendance experience and self-claimed free of dental phobia were recruited in this cross-sectional study, with their dental anxiety level assessed by SDAxI. Functional magnetic resonance imaging recorded their brain signals in response to audiovisual footages resembling dental scaler or turbine in action. After the brain imaging, they gave fear ratings to the footages in visual analog scale (VAS). Results: Participants’ SDAxI scores positively correlated with their responses in the insular cortex (r2 = 0.388–0.445, P < 0.005). Their SDAxI scores also positively correlated with their fear ratings of the footages (r2 = 0.415–0.555, P < 0.005). Discussion: Our findings indicated a possible neurobiological relevance of SDAxI, and reinforced its neurobiological validity in assessing dental anxiety level of dental attenders.